TEKNIK PENGAMBILAN GAMBAR SINEMATOGRAFI 5C PADA VIDEO COMPANY PROFILE WEB SERIES CAFÉ HALAMAN OMAH - Syahputra, Arief Kurniawan; Budi Priatna, Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of social media has encouraged SMEs to utilize company profile videos as a visual promotional medium capable of increasing brand awareness and audience engagement. This study aims to analyze the application of filming techniques by the cameraman in the production of the Café Halaman Omah web series company profile video using Joseph V. Mascelli’s 5C theory of cinematography: camera angle, close-up, composition, continuity, and cutting. The method used is qualitative descriptive, employing data collection techniques such as observation, interviews, documentation, literature review, and the author’s active participation as a cameraman in the production process. The output consists of four episodes of the web series published via Instagram Reels in a 9:16 vertical format. The results indicate that the application of the 5C cinematography techniques produces visuals that are aesthetically pleasing, communicative, and support the conveyance of Café Halaman Omah’s identity as a warm, comfortable, and community-oriented space. The use of eye-level angles helps create a natural feel, close-ups enhance the conveyance of emotions and product details, composition builds visual balance, continuity maintains the flow of the narrative, and editing helps create a dynamic visual rhythm. Thus, the application of appropriate filming techniques is deemed effective in enhancing the visual quality of the company profile video while supporting Café Halaman Omah’s branding process through Instagram.